Critical Thinking Disposition of Prospective Mathematics Teacher in Solving Mathematics problem - Asyika, Samsul Irpan; Abd Qohar; Erry Hidayanto; Hery Susanto; Lalu Indar Anggara Putra (Yayasan Nurul Yakin Bunga Tanjung, 2026)
Truth-seeking and open-mindedness are core dispositions of critical thinking, particularly in the context of mathematical problem solving. This study examines the critical thinking dispositions of prospective mathematics teachers when solving problems containing contradictory information and incomplete data. Specifically, it investigates behavioral tendencies related to truth-seeking and open-mindedness.This qualitative exploratory study involved 15 prospective mathematics teachers. Data were collected through written tests, direct observations, and semi-structured interviews. To enhance validity, methodological triangulation was employed by comparing findings across these three data sources to ensure consistency and credibility. The findings indicate that the participants generally did not demonstrate strong truth-seeking dispositions. Most participants failed to question the validity or completeness of the information presented and tended to respond procedurally without critically examining contradictions or missing data. These results suggest that procedural competence does not necessarily reflect the presence of critical thinking dispositions. The study highlights the need for instructional strategies that explicitly foster truth-seeking and open-mindedness in mathematics teacher education.